2016
DOI: 10.1261/rna.051490.115
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of the structural and catalytic roles of Rrp6 in exosomal degradation of individual mRNAs

Abstract: The RNA exosome is a conserved complex for RNA degradation with two ribonucleolytic subunits, Dis3 and Rrp6. Rrp6 is a 3 ′ -5 ′ exonuclease, but it also has a structural role in helping target RNAs to the Dis3 activity. The relative importance of the exonuclease activity and the targeting activity probably differs between different RNA substrates, but this is poorly understood. To understand the relative contributions of the exonuclease and the targeting activities to the degradation of individual RNA substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The exosome is the main pathway for RNA degradation and is involved in RNA trimming during maturation 40 . The gene rrp6 encodes for a 3′-5′ exo-ribonuclease subunit of the exosome 41 . The deletion of rrp6 resulted in the recovery of TER1 expression in lar7 ∆ cells, close to wild-type level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The exosome is the main pathway for RNA degradation and is involved in RNA trimming during maturation 40 . The gene rrp6 encodes for a 3′-5′ exo-ribonuclease subunit of the exosome 41 . The deletion of rrp6 resulted in the recovery of TER1 expression in lar7 ∆ cells, close to wild-type level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One line of evidence supporting this is that degradation of poly(A) + transcripts that accumulate in yeast strains lacking Rrp6 can be partially rescued by expressing catalytically inert Rrp6 (Assenholt et al 2008;Mukherjee et al 2016). Furthermore, in vitro studies showed that Rrp6 protein can activate the RNA decay activities of Dis3, especially evident for substrates with poly(A) tails Lima 2012, 2017;Wasmuth et al 2014).…”
Section: Rrp6 Conformations and Rna Pathsmentioning
confidence: 96%
“…Accordingly, when an RNA substrate is engaged in the exosome central channel path to Dis3, Rrp6 is unable to bind another substrate ( 14 ). In addition, Rrp6 appears to contribute to efficient elimination of polyadenylated substrates by Dis3 ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%